Reusability of plastics - Sing Peir Ming (Universiti Malaysia Perlis, 2008)
It is a challenge to reduce the ever-increasing flow of plastics waste. This study was undertaken to investigate the viability of recycling plastics products and their capabilities in substituting virgin plastics in the remaking of plastics products so reduce waste and to reduce energy usage. Experiments were carried out in laboratory in which virgin Polypropylene and High Density Polyethylene were injection moulded and the subsequent products were recycled and reproduced by injection moulding process again. Parameters that were studied including injection moulding temperature and cooling time. The mixture of both plastics was also experimented to study the feasibility of mixing two different plastics in the making of plastics products. Tensile test was conducted in order to understand how tough the material was in the remaking process. Recycled parts were able to be reproduced by the injection moulding process without any significant physical variation from their mechanical properties compared to the virgin material. However, recycled parts were generally less tension resistant if compared to their original parts. Polypropylene was proven to be the toughest plastics amongst all the plastics tested with tensile strength as high as 22.6852 N/mm2.